2016
DOI: 10.14739/2310-1210.2016.2.69328
|View full text |Cite
|
Sign up to set email alerts
|

Relations Gln27Glu polymorphism β2-adrenoceptor gene with bronchial asthma

Abstract: Зв'язок Gln27Glu поліморфізму гена β2 -адренорецептора з бронхіальною астмоюСумський державний університет, медичний інститут, м. Суми Ключові слова: бронхіальна астма, поліморфізм генетичний, рецептори адренергічні.Мета роботи -аналіз наукової літератури стосовно зв'язку Gln27Glu поліморфізму гена β2-адренорецепторів із розвитком, ступенем тяжкості та рівнем контролю бронхіальної астми (БА).Результати. У статті здійснений аналіз даних фахової літератури щодо ризику розвитку, ступеня тяжкості та рівня контролю… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…This substantial difference in the genotypes distribution for the Gln27Glu polymorphism concerning the age of disease onset provided the basis for a differentiated analysis of risks of early and late-onset asthma phenotypes. The results we obtained in the previous study involving the smaller population of examined asthma patients (195) showed that the Glu27Glu genotype carriers have twice a risk of asthma developing (OR = 1.99; 95% CI = 1.14-3.47; p = 0.03) as the carriers of the Gln27Gln genotype [15]. The risk estimation (n = 553), regardless of the phenotypes and with regard to the studied polymorphism, showed a significant association related to the following models of inheritance: dominant (р = 0.01), super-dominant (р = 0.01), and additive (р = 0.02).…”
Section: Discussionmentioning
confidence: 46%
“…This substantial difference in the genotypes distribution for the Gln27Glu polymorphism concerning the age of disease onset provided the basis for a differentiated analysis of risks of early and late-onset asthma phenotypes. The results we obtained in the previous study involving the smaller population of examined asthma patients (195) showed that the Glu27Glu genotype carriers have twice a risk of asthma developing (OR = 1.99; 95% CI = 1.14-3.47; p = 0.03) as the carriers of the Gln27Gln genotype [15]. The risk estimation (n = 553), regardless of the phenotypes and with regard to the studied polymorphism, showed a significant association related to the following models of inheritance: dominant (р = 0.01), super-dominant (р = 0.01), and additive (р = 0.02).…”
Section: Discussionmentioning
confidence: 46%